Advancements in imaging research in thyroid-associated ophthalmopathy - Xu, Zuxing; Xue, Zhe; Lyu, Zhaohui (Frontiers in Endocrinology, 2025)
Thyroid-associated ophthalmopathy (TAO), a sight-threatening ocular condition intricately associated with autoimmune thyroid diseases, is the most common orbital disorder among adults. Accurate assessment of TAO is crucial for effective clinical management. However, the current evaluation system is hindered by significant subjectivity and a lack of standardized objective criteria, thereby complicating the pursuit of precise and individualized treatment strategies. Imaging techniques are integral to the clinical management of TAO, as they provide detailed anatomical visualization of the orbit and reflect underlying pathophysiological changes. This article reviews the applications of three prevalent imaging modalities—ultrasonography, computed tomography (CT), and magnetic resonance imaging (MRI)—in the diagnosis and management of TAO. We examine their respective advantages, limitations, and roles in disease diagnosis, staging, and evaluation of therapeutic efficacy, with the aim of providing a scientific basis for the optimization of clinical practice.